Penggunaan Metode Saw Dalam Mendukung Pengambilan Keputusan Penentuan Pemberian Pinjaman (Studi Kasus : Koperasi Hening Rahayu) - Indrayanti, Ni Made Ayu Sonya; Suarnatha, I Putu Dody; Putra, I Gede Jana Adi (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2023)
This research aims to implement the SAW (Simple Additive Weighting) method in supporting decision making for granting money loans to Savings and Loans Cooperatives. Hening Rahayu Savings and Loans Cooperative in Tabanan, Bali is the subject of this research. In this context, cooperatives face challenges in selecting customers who are worthy of loan services. The SAW method was chosen because of its ease of implementation and its ability to consider various relevant criteria. This method has advantages in terms of usability, error, interpretability, and computational efficiency. This research will involve collecting data on the profile of potential borrowers, loan eligibility, credit risk, and repayment capacity. This data will be analyzed using the SAW method to produce a final score for each prospective borrower. This score will be used as a basis for making decisions about granting loans. By using the SAW method, it is hoped that the Hening Rahayu Cooperative can speed up and simplify the decision-making process regarding granting loans. It is hoped that the results of this research can contribute to the development of technology in the savings and loan cooperative sector. Further research could involve developing other methods to support decision making or making the SAW method a system that can support decision making in different savings and loan cooperative contexts.